Unit Cost Perawatan Gigi di Klinik Fanisa Kota Pariaman dengan Metode Activity Based Costing - Hidayati Hidayati; Febrian Febrian; Lendrawati Lendrawati; Kosno Suprianto (Andalas Dental Journal, 2023)
Objective: To find out unit cost of dental health service in Pariaman City Fanisa Clinic using the Activity Based Costing method in era of national health insurance. Method : This research was a quantitative descriptive study that used was Activity Based Costing (ABC) used mathematical calculations. Results : The results of this study indicated there was 8 dental health service in Fanisa Clinic in Pariaman City in 2018 and the unit cost for each service was consultation Rp.55.945, permanent tooth extraction Rp.127.825, extraction of deciduous teeth Rp.79.311, composit resin patching Rp.156.384, GIC patching Rp.145.843, scalling Rp.131.358, premedication Rp.61.291 and pulp capping Rp.107.729. Conclusion: The highest unit cost for dental health services at the Fanisa Clinic in Pariaman City was composite resin patching service and the lowest was consulting services. The average unit cost of dental health services at the Fanisa Clinic in Pariaman City was Rp.108.211. The biggest cost in the production unit was the cost of employee salary.